22 Evaluation of Current US Swine Selection Indexes and Indexes Designed for Chinese Pork Production. (10th April 2018) - Cheng, J; Newcom, D W; Schutz, M M; Schinckel, A P
Abstract: The objective was to compare selection indexes based on the production costs and economic values from the United States and China. Indexes with dollar values including terminal sire (TSI), maternal line (MLI) and sow productivity (SPI) indexes were calculated based on the production costs and market prices for the U.S. and China. Estimated breeding values for: days to 113.5 kg, backfat depth, loin muscle area, number born alive, number weaned, litter weight adjusted to 21 days, days from weaning to estrus, and litter birth weight were provided by a Chinese pig breeding company to evaluate alternative STAGES indexes. The Duroc data included 39 sires, 5, 079 boars and 5, 368 gilts. The Landrace data included 199 dams, 83 sires, 2, 749 boars and 2, 750 gilts. The Yorkshire data included 1, 368 dams, 139 sires, 18, 481 boars and 17, 962 gilts. The means, standard deviations, and correlations for the EBV's and indexes were calculated. The Chinese TSI values were more highly correlated (R = 0.97 to 0.99, P<0.001) with the U.S. indexes than the MLI values (R=0.92 to 0.97, P<0.001). Overall, the Chinese indexes had greater SD's (TSI, 58 to 87% greater; SPI, 22 to 26% greater; MLI, 43 to 76% greater). The TSI's were all highly correlated (R > 0.98, P<0.001) with feed efficiency. The Chinese MLI values had greater correlations with TSI and lesser correlation with SPI than the U.S. indexes. The Chinese MLI placed greater emphasis and subsequently greater predicted rates of genetic progress for the post weaning traits and lesser emphasis on sow productivity traits than current U.S. MLI. Alternative Chinese indexes were evaluated with or without market value based on carcass lean percentage. In the U.S., the carcass value was determined based on the curvilinear economic relationship between carcass value and lean percentage. The Chinese TSI including carcass value relative to carcass lean percentage placed greater emphasis on carcass leanness traits (backfat depth and loin muscle area) with less emphasis on growth rate than the Chinese TSI without carcass premium for carcass lean percentage. The Chinese MLI including carcass value relative to carcass lean percentage also placed greater emphasis on the carcass leanness traits with less emphasis on growth rate and reproductive traits (number born alive, number weaned and litter weight adjusted to 21 days) than the Chinese MLI with no carcass premium for carcass lean percentage. The greater Chinese feed cost results in greater emphasis for feed efficiency.